Optimal management of pulmonary arterial hypertension: prognostic indicators to determine treatment course - Baldi F; Fuso L; Arrighi E; Valente S (Dove Medical Press, 2014)
Fabiana Baldi, Leonello Fuso, Eugenio Arrighi, Salvatore Valente Pulmonary Medicine Unit, Catholic University, Rome, Italy Abstract: Pulmonary arterial hypertension (PAH) is a rapidly progressive pulmonary vascular disease with a multifactorial etiopathogenesis that can result in right-sided heart failure and death. A number of studies indicate that an early therapeutic intervention yields better results on disease progression as compared to delayed treatment. In this review, we will analyze treatment strategies that may be used for monitoring disease progression and for guiding treatment decisions. Several factors (ie, symptoms, functional class, exercise capacity as assessed by a walking test and cardiopulmonary stress testing, hemodynamic parameters, cardiac magnetic resonance imaging, and plasma levels of biochemical markers) have been prognostic of survival. These indicators may be used both at the time of diagnosis and during treatment follow-up. No resolutive therapy is currently available for PAH; however, in the last decade, the advent of specific pharmacological treatments has given new hope to patients suffering from this debilitating disease with a poor prognosis. Combination drug therapies offer increased benefits over monotherapy, and current guidelines recommend a sequential “add on” design approach for patients in functional class II–IV. The goal-oriented “treat to target” therapy sets the timing for treatment escalation in case of inadequate response to currently known prognostic indicators. To date, further longitudinal studies should be urgently conducted to identify new goals that may improve therapeutic strategies in order to optimize personalized treatment in PAH patients. Keywords: pulmonary hypertension, prognostic indicators, specific drug therapy, disease progression